2021
DOI: 10.2217/epi-2020-0353
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation of Autophagy Genes Linked to Diabetic Nephropathy by Administration of Isorhamnetin in Type 2 Diabetes Mellitus Rats

Abstract: Aim: To assess isorhamnetin efficacy for diabetic kidney disease in a Type 2 diabetes mellitus rat model, through investigating its effect at the epigenetic, mRNA and protein levels. Materials & methods: Type 2 diabetes mellitus was induced in rats by streptozotocin and high-fat diet. Rats were treated with isorhamnetin (50 mg/kg/d) for 4 or 8 weeks. Fasting blood glucose, renal and lipid profiles were evaluated. Renal tissues were examined by light and electron microscopy. Autophagy genes ( FYCO1, ULK, TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Kaempferol restrains the processes of oxidative stress, inflammatory response, and fibrosis 35 , promotes insulin release 36 . By inhibiting the NF-κB signaling pathway, isorhamnetin interferes the expression of downstream TNF-α, IL-1β, IL-6, intercellular adhesion molecule-1 (ICAM-1), and TGF-β1, thereby alleviating the inflammatory response and oxidative stress 37 , improving fasting blood glucose and lipid metabolism, and protecting kidney 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol restrains the processes of oxidative stress, inflammatory response, and fibrosis 35 , promotes insulin release 36 . By inhibiting the NF-κB signaling pathway, isorhamnetin interferes the expression of downstream TNF-α, IL-1β, IL-6, intercellular adhesion molecule-1 (ICAM-1), and TGF-β1, thereby alleviating the inflammatory response and oxidative stress 37 , improving fasting blood glucose and lipid metabolism, and protecting kidney 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Formononetin improved oxidative stress and prevented the progression of renal fibrosis in DN by activating the Nrf2/ARE signaling pathway [ 43 ]. Experimental studies have shown that isorhamnetin has renoprotective effects on DN through improving fasting blood glucose, increasing autophagosomes in renal tissues, and suppressing miRNA regulation of autophagy genes [ 44 ]. Besides, isorhamnetin inhibits oxidative stress, inflammation, and apoptosis in STZ-induced diabetic rats [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking, a method of analyzing the binding site and affinity between the conformation of molecules and macromolecular targets, has been considered a crucial technique for structure-based drug discovery [ 40 ]. The core DN-related genes targeted by the AR-PN herb pair bioactive components was identified according to the component-target-pathway network, which were further validated by molecular docking with the experimentally verified AR-PN herb pair bioactive components possessing renoprotective effects on DN, including quercetin [ 41 ], kaempferol [ 42 ], formononetin [ 43 ], and isorhamnetin [ 44 ]. First, the mol2 formats of these bioactive components were obtained from the TCMSP database and PubChem database, which were converted to the format of pdb and pdbqt via Pymol software and AutoDock Tools 1.5.6, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Isohamnetin administration in T2DM rats restored adipose tissue and myofibrils architecture and downregulated mTOR, IGF1R and AKT in the skeletal muscle and adipose tissue. In addition, an increase in miR-1 and miR-1363 expression was also reported, associated with reduced expression of LncRNA-RP11-773H22.4 [ 228 ]. Moreover, diabetic nephropathy conditions were also significantly attenuated, accompanied with the epigenetic modulation (miR-15b, miR-34a and miR-633)-mediated activation of autophagy-related genes (FYCO1, ULK, TECPR1 and WIPI2) and autophagosome formation [ 229 ].…”
Section: Roles Of Polyphenols In Autophagic Adaptation For Healthy Agingmentioning
confidence: 99%